A simple chip free-flow electrophoresis for monosaccharide sensing via supermolecule interaction of boronic acid functionalized quencher and fluorescent dye - Yin, Xiao-Yang; Dong, Jing-Yu; Wang, Hou-Yu; Li, Si; Fan, Liu-Yin; Cao, Cheng-Xi (Electrophoresis, 2013)
Here, a simple micro free‐flow electrophoresis (μFFE) was developed for fluorescence sensing of monosaccharide via supermolecule interaction of synthesized boronic acid functionalized benzyl viologen (ο‐BBV) and fluorescent dye. The μFFE contained two open electrode cavities and an ion‐exchange membrane was sandwiched between two polymethylmethacrylate plates. The experiments demonstrated the following merits of developed μFFE: (i) up to 90.5% of voltage efficiency due to high conductivity of ion‐exchange membrane; (ii) a strong ability against influence of bubble produced in two electrodes due to open design of electrode cavities; and (iii) reusable and washable separation chamber (45 mm × 17 mm × 100 μm, 77 μL) avoiding the discard of μFFE due to blockage of solute precipitation in chamber. Remarkably, the μFFE was first designed for the sensing of monosaccharide via the supermolecule interaction of synthesized ο‐BBV, fluorescent dye, and monosaccharide. Under the optimized conditions, the minimum concentration of monosaccharide that could be detected was 1 × 10−11 M. Finally, the developed device was used for the detection of 0.3 mM glucose spiked in human urine. All of the results demonstrated the feasibility of monosaccharide detection via the μFFE.